Scenarios in Public Administration: Critical Thinking Exercises - Daniello, Robert J.; Laubsch, Paulette M. (Hamilton Books, 2008)
Scenarios in Public Administration focuses on the broad topics of leadership, human relationship management, technical, administrative, and political concepts for students of public administration. There are many individuals who have the technical proficiencies and are administratively competent, but they do not possess the political skills needed to succeed. Political influence is frequently learned on the job, and the process is a long one. By adding the political element, this work goes beyond the normal coursework taught in MPA and related programs. This collection can be used throughout the MPA program in a number of courses, including Public Policy Analysis, Personal Administration, and Seminar of Public Administration.